MAIN FACTORS OF PHYSICAL DEVELOPMENT AND SPORTS FITNESS OF 15-16-YEAR-OLD BASKETBALL PLAYERS - Yavor Asparuhov; Mariana Borukova (Journal of Applied Sports Sciences)
It is often needed in basketball practice to evaluate the stage of the young basketball players‘ preparation. In this way the necessary information is received which serves as a landmark about the level of their development – whether they have the necessary physical qualities and basketball skills, whether they go forward within the educational and training process and whether there is a perspective for their development as highly qualified competitors in the future. The disclosure of the factor structure of the physical development and the specific workability of growing up basketball players has high informative value for the optimization of the educational and training process. The aim of the study is to optimize the training process for growing basketball players by revealing the factor structure and identifying the main factors of sports preparedness in the age range of 15-16 years. The subject of research is the sports training of growing basketball players. The object of the study is the signs of physical development, the special physical and specific techno-tactical preparation. The research was done among 65 basketball players (15-16 years old). Sport and pedagogical tests as per 20 indicators, bearing information about the basic symptoms of the physical development and the specific basketball workability, were made for the needs of the study. The results of the tests were subjected to processing by descriptive statistics, correlation and factor analysis. Results: At the beginning of the study, seven main factors were identified that characterize the specific preparedness in basketball, while at the end of the study, the derived components were five.